Multiple adiabatic beds for efficient conversion of CO2-containing syngas to dimethyl ether - Hatipoğlu, Ceren. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
DME is considered for replacing its conventional counterparts due to its attractive properties such as CO+NOx free combustion characteristics. DME production involves exothermic equilibrium reactions, namely synthesis gas-to-methanol conversion and subsequent dehydration of methanol, necessitating the use of synthesis and solid acid catalysts, respectively. The co-existence of catalysts in the same reactor is called direct DME synthesis, which is limited by thermodynamic effects induced by increased temperatures and H2O generated during the process. A novel reactor strategy to overcome thermodynamic constraints is the so-called multiple adiabatic beds which involve adiabatic packed-bed reactors interconnected with microchannel heat exchangers. The microchannel heat-exchangers, selected for their inherently high heat transfer rates and compact characteristics, are used to decrease temperature for the successive beds. When equipped with a steam-selective membrane, the heat-exchangers also used to remove H2O from the reactive mixture. Reactors include 1:1 (by mass) physical mixtures of to each bed CZA+!-Al2O3, or CZA+HZSM-5 catalysts. Packed-bed reactors are simulated by the steady-state 1D pseudo-homogeneous reactor model involving literature-based reaction kinetics. Modeling of the microchannel heat-exchangers, however, are carried out by solution of the Navier-Stokes equations along with heat transport at 2D steady-state under ANSYS platform. The effects of inlet temperature, pressure and the amount of catalyst are studied in the range of 493-513 K, 20-60 bar and 0.15-0.18 kg catalyst respectively. The results show that the proposed reactor strategy offers the potential of relaxing the characteristic thermodynamic constraints of one-step DME synthesis.
Keywords: Methyl ether.